Stable isotope (δ13C and δ18O) and element/Calcium ratios of Pleistocene planktic foraminifers (G. bulloides, N. pachyderma sin.) of core SO264_55-1 - Dirk Nürnberg; Nadine Gehre; Sebastian Fessler (PANGAEA, 2025)
Sediment cores from the volcanic Emperor Seamount Chain obtained during RV SONNE cruise SO264 (SONNE-EMPEROR) in August 2018 allow us to reconstruct lateral changes in the subarctic and subtropical gyres in the pelagic North Pacific over the last ~0.5 million years. This dataset comprises planktic stable carbon (δ13C) and oxygen isotope (δ18O) data, as well as foraminiferal element/Calcium ratios from gravity core SO264_55-1, which was recovered from Minnetonka Seamount (47°10.542 N 169°25.292 E) from 2936 m water depth. Measurements were performed on the planktic foraminiferal species Globigerina bulloides and Neogloboquadrina pachyderma sinistral. Sampling and analytical studies were carried out from 0.005–16.105 m core depth at ~2 cm spatial resolution. The isotope analyses were performed on a Thermo Scientific MAT 253 mass spectrometer with an automated Kiel IV carbonate preparation device. Trace metal analyses were performed on a VARIAN 720-ES Axial ICP-OES.